MICELLE-MEDIATED EXTRACTION AS A TOOL FOR SEPARATION AND PRECONCENTRATION IN COPPER ANALYSIS - F. Ahmadia; A. Khanmohammadi; A. Malekpour (Universitas Gadjah Mada, 2007)
A cloud point extraction method was presented for preconcentration of copper in various samples. After complexation with 4-Amino-2,3-dimethyl-1-phenyl-3-pyrazoline-5-one (ADPP) or N-Benzoyl-N-phenylhydroxylamine (BPA) in water, analyte ions are quantitatively extracted to the phase rich in Triton X-114 after centrifugation. 2.0 mol L-1 HNO3 solution in methanol was added to the surfactant-rich phase prior to its analysis by flame atomic absorption spectrometry (FAAS). The adopted concentrations for ADPP, Triton X-114, HNO3 and parameters such as bath temperature, centrifuge rate and time were optimized. Detection limits (3SDb/m) of 1.3 and 1.9 ng mL-1 for ADPP and BPA along with enrichment factors of 30 and 38 for ADPP and BPA were achieved. The high efficiency of cloud point extraction to carry out the determination of analyte in complex matrices was demonstrated. The proposed method was applied to the analysis of biological, industrial, natural and wastewater, soil and blood samples.